Macrofaunal bioturbation attributes in relation to riverine influence: What can we learn from the Po River lagoonal system (Adriatic Sea)?. (5th January 2020) - Nasi, F.; Ferrante, L.; Alvisi, F.; Bonsdorff, E.; Auriemma, R.; Cibic, T.
Abstract: Delta areas are highly dynamic transitional areas, important for burial and decomposition of terrestrial and marine organic matter (OM). In these environments, macrofaunal organisms are influenced by fluctuations of fresh OM inputs that modify several aspects of their growth, reproduction and behaviour. Macrofaunal bioturbation activities are significant processes performed by individuals, which directly influence the biogeochemical cycling and thus the ecosystem functioning. To assess the influence of terrigenous/freshwater OM on bioturbation attributes of macrofauna in a lagoonal system, we integrated the bioturbation and irrigation potential (BPc and IPc ) community indices and functional traits linked to reworking and ventilation of sediments (using Biological Traits Analysis-BTA). The macrofaunal community was investigated in four lagoons (Caleri, Marinetta-Vallona, Canarin and Scardovari) of the Po River Delta in Italy (northern Adriatic Sea). We examined the macrofaunal biodiversity and bioturbation attributes in relation to grain-size distribution, carbon and nitrogen ratio (C:N), carbon and nitrogen stable isotopes (δ 13 C and δ 15 N), and the radionuclides 137 Cs and 7 Be. The latter were used as proxies of the age of terrigenous/riverine-derived OM. The lowest values of BPc and IPc that corresponded to minimum values of benthic biodiversity were observed at the inner sampling stations of Scardovari. Here, low diversity values were likely ascribed to recent hypoxic/anoxic conditions exacerbated by the low water renewal that characterizes this lagoon, influencing the bioturbation processes. Grain-size fractions were significant drivers of the differences in BPc and IPc, and the major number of taxa in coarse sediments contributed to the highest values of bioturbation indices. A significant difference in IPc between sandy and muddy stations was due to the presence of subsurface deposit feeders with high burrowing depths and blind-ended burrows that enhanced the bio-irrigation in coarse sediments. We observed diverse spatial patterns of trait-categories belonging to sediment reworking activity at stations differently influenced by freshwater OM. Semi-motile and conveyor invertebrates, that are able to move sediment particles through their gut by ingestion and secretion, were dominant nearby the lagoon mouths where OM of freshwater origin was present. High occurrence of motile and biodiffuser invertebrates, that can randomly mix sediments layers, were found at stations characterized by old OM. Macrofaunal sediment reworking and ventilation processes are of paramount importance in the framework of an efficient management and sustainable use of lagoons, often exposed to anoxic and dystrophic events, that are strongly exploited for aquaculture. Highlights: Macrofaunal bioturbation is related to freshness and origin of organic matter (OM). Confinement gradient and grain-size affect bioturbation in coastal lagoons. The trait conveyor is highly influenced by the enrichment of allochthonous OM. The trait biodiffuser prevailed in the presence of old OM of freshwater origin. Reworking and ventilation are key processes in anoxic lagoon used for aquaculture.